Health Interventions for Health Promotion in Sub-Saharan Africa: Assessing Impact on Health Literacy and Comparative Analysis of Online Communication Channels - Ogweno, Stephen; Harrison, Roger; Bonface, Otieno; Murithi, Bernard (British Journal of Healthcare and Medical Research, 2025)
Introduction: Considering the increased incidence of noncommunicable diseases (NCDs) and the need for novel approaches to health promotion, this study investigates the feasibility of cross-country mHealth interventions in Sub-Saharan Africa. The study, which focuses on using digital platforms for health communication, intends to investigate the feasibility and effectiveness of cross-country mhealth interventions aimed at disseminating health promotion materials in Sub-Saharan Africa across various platforms. The study is based on the NCDs 365 project, a year-long health promotion initiative in five nations aimed at promoting NCD literacy. Methodology: The study utilized a multi-stage sample technique, including an intentional selection of five nations (Cameroon, Kenya, Nigeria, Uganda, and Zimbabwe) with active local partner organizations conducting the initiative. The following stage was convenience sampling of members of these organizations who participated in the NCD365 project activities. Data gathering included the distribution of questionnaires via local partners, followed by thorough analysis using descriptive techniques and comparison tests such as ANOVA and the Kruskal-Wallis test. The extensive methodology ensured a broad and representative sample, which increased the findings’ validity and generalizability. Results: The findings demonstrated the potential of mHealth interventions to close health literacy gaps and promote positive health behaviors throughout Sub-Saharan Africa. According to an analysis of online communication platform usage, WhatsApp was the most popular (58.6%), followed by X (20.8%) and Facebook (6.8%). The study also found significant trends in platform preference across all five countries. Furthermore, gender-specific study indicated comparable literacy rates, with males slightly outperforming females. The Kruskal-Wallis test found no significant difference in the efficacy of various online communication channels for health promotion, confirming the viability of cross-country mHealth programs. Conclusions: This study highlights the significant potential of cross-country mHealth interventions for health promotion in Sub-Saharan Africa. The study’s strong methodology, agreement with current research, and gender-specific analysis add to its dependability and credibility. The findings of this analysis provide significant recommendations to policymakers seeking to optimize platform-specific policies and stimulate cross-country collaborations in health promotion. Finally, these findings expand the discussion on health literacy promotion and establish the groundwork for evidence-based recommendations that might drive effective health communication initiatives in the region and beyond.